2019
DOI: 10.1111/jphp.13081
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 increases CHSY-1 expression in aortic endothelial cells via transactivation of transforming growth factor β type I receptor induced by type B receptor endothelin-1

Abstract: Objectives TGF‐β through hyperelongation of glycosaminoglycan (GAG) chains leads to binding of low‐density lipoproteins to the proteoglycans. The vasoactive peptide, endothelin‐1 (ET‐1), plays a key role in the development of atherosclerosis. This study addressed the question whether ET‐1 by activating the Rho kinase and cytoskeletal rearrangement can transactivate the TGF‐β receptor leading to phosphorylation of the transcription factor Smad2 and increased expression of the GAG chain synthesizing enzyme such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…These findings provide a better understanding of the signaling pathway controlling the length of proteoglycan GAG that promotes lipoprotein binding in the vessel wall and the development of atherosclerosis 43 . Furthermore, endothelin-1 signaling via ETB receptor (endothelin-1 type B receptor) utilizes cytoskeletal rearrangements and Rho (ROCK) kinase, but not map, leading to transactivation signaling of TβRI (transforming growth factor beta type I receptor) and phosphorylation of Smad2C, and increases CHSY-1 levels via this pathway 44 . In addition, a recent study on rat retinal microvascular endothelial cells (rrmec) showed that hyperglycemia in rrmec leads to significantly elevated mRNA levels of GAG biosynthetic enzymes (including extl -1,2,3, ext -1,2, chsy -1,3, and has2,3), and that these elevations may be a compensatory response to overall glycocalyx loss 45 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings provide a better understanding of the signaling pathway controlling the length of proteoglycan GAG that promotes lipoprotein binding in the vessel wall and the development of atherosclerosis 43 . Furthermore, endothelin-1 signaling via ETB receptor (endothelin-1 type B receptor) utilizes cytoskeletal rearrangements and Rho (ROCK) kinase, but not map, leading to transactivation signaling of TβRI (transforming growth factor beta type I receptor) and phosphorylation of Smad2C, and increases CHSY-1 levels via this pathway 44 . In addition, a recent study on rat retinal microvascular endothelial cells (rrmec) showed that hyperglycemia in rrmec leads to significantly elevated mRNA levels of GAG biosynthetic enzymes (including extl -1,2,3, ext -1,2, chsy -1,3, and has2,3), and that these elevations may be a compensatory response to overall glycocalyx loss 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The GPCR agonist, endothelin-1 (ET-1), signals via ET-1 receptors (ET A and ET B ) to transactivate the TGFBR, leading to the phosphorylation of Smad2 carboxyl terminal in human vascular smooth muscle cells [ 129 ], bovine aortic endothelial cells [ 130 , 131 ] and rat alveolar epithelial cells [ 132 ]. Different ET-1 receptors are involved in the transactivation of the two cell types.…”
Section: Transactivation Of Tgfbr By Different Receptor Signaling Pat...mentioning
confidence: 99%
“…Different ET-1 receptors are involved in the transactivation of the two cell types. ET A receptor transactivates TGFBR in rat alveolar epithelial cells [ 132 ], whereas ET B is the responsible receptor in bovine aortic endothelial cells [ 130 ]. In bovine aortic endothelial cells, ET A recruits ROCK to trigger cytoskeleton rearrangement to activate TGFBR [ 130 ].…”
Section: Transactivation Of Tgfbr By Different Receptor Signaling Pat...mentioning
confidence: 99%
“…For experiments, VSMCs were seeded into 35 mm dishes (qRT-PCR and Western blot experiments) at a density of 4 Â 10 5 / well and grown to confluency and then confluent cultures were serum starved for 24 h by incubation in DMEM/F12 medium containing 0.1% (v/v) FBS and 1% penicillin-streptomycin before experimentation. VSMCs were pre-incubated with inhibitors (bosentan (20 μM), 35 SB431542 (10 μM) 36 and SB239063 (20 μM) for 30 min, NAC (10 mM) 37 for 1 h, DPI (20 μM) and apocynin (20 μM) 37 for 2 h and then exposed to ET-1 (100 nM) 13,38 or TGF-β (2 ng/ml). 39 VSMCs used in experiments were between passages 10-20.…”
Section: Culture Of Human Aortic Smooth Muscle Cellsmentioning
confidence: 99%